THE ROLE OF FAMA - FRENCH THREE FACTOR MODEL IN THE ESTIMATED RATIO OF THE STOCK RETURNS IN THE VIETNAM SECURITIES MARKET - Vu Thi Phuong Thao (Journal of Applied Science and Technology, 2019)
Stock returns are important information for investors in the stock market. To help determine profitability and risk in securities investment, there are many asset valuation models on the market. However, studies over the years show that the model of FAMA - FRECH is more suitable and better explains the rule of profitability and risk of stocks. Specifically, the three factors of the model show a positive or negative correlation with the profitability of the stock, which better explains the influence of factors on the stock return rate. with other models such as CAPM model, 5-factor model FAMA - FRENCH